Mycenaean and Near Eastern Economic Archives - Uchitel, Alexander (2012)
Ph.D. Dissertation; Department of Ancient History; Supervisors: James T. Hooker and Amelie Kuhrt; Linear В records of (male/female) work teams; Ur III documents for the quotas of conscripts from specific villages; Ugaritic texts dealing with land tenure and organisation of cultic personnel; cuneiform Hittite and hieroglyphic Luwian texts (Kululu lead strips)